Prebiotics Do Not Influence the Severity of Atopic Dermatitis in Infants: A Randomised Controlled Trial. - Jan Boženský; Martin Hill; Richard Zelenka; Tomáš Skýba (PLoS ONE)
Unlabelled The objective was to evaluate the effects of a hypoallergenic (HA) formula supplemented with prebiotic galacto-oligosaccharides on the severity of atopic manifestations. A randomised clinical trial was conducted. The control group was infants, fed with hypoallergenic formula and without supplementation. The duration of the study was six months. The primary outcome of the study was a difference in the severity of atopic dermatitis measured using SCORAD (Scoring Atopic Dermatitis) criteria. Secondary outcomes were anthropometry (length, weight, and head circumference), together with the tolerance and incidence of infections. Both groups showed a decrease of average SCORAD values, but no statistically significant difference between the evaluated groups was observed. There were no statistically significant differences in anthropometry, or the tolerance or incidence of infections. Although there is no evidence, that consumption of a hypoallergenic infant formula enriched with prebiotic galacto-oligosaccharides had any effect on SCORAD, it was safe and well tolerated. Trial registration www.clinicaltrials.gov NCT 02077088.